DR. BHIM RAO AMBEDKAR’S ADVOCACY OF WOMEN RIGHTS - Rashid Manzoor Bhat (RADJA PUBLIKA, 2023)
Dr. Ambedkar, who was a strong fighter and a wise scholar, has done a lot to move society toward Liberty, Equality, and Brotherhood. He was the first Indian to break down barriers that kept women from getting ahead in India. By writing down the common Civil Code for Hindus and other parts of Indian society, he laid the groundwork for real and honest work. In this paper, we try to show what Dr. Ambedkar thought about women's problems in India before and after it became independent, as well as how they still matter today. Dr. Ambedkar started his movement in 1920. He made a lot of noise about how bad the Hindu social order was. In 1920, he started the journal Mook Nayak, and in 1927, he started Bahiskrit Bharat. Through its topics, he drew attention to the problems of women and the need for education, as well as the problems of the depressed. Radhabai Vadale's speech at a press conference in 1931 showed how Dr. Ambedkar tried to give women the confidence to speak up. In the Bombay Legislative Assembly, he pushed hard for measures to help women plan their families. Dr. Babasaheb worked his whole life to help women, even those who were involved in bad things like prostitution. Ambedkar made poor, illiterate women aware of their rights and gave them the motivation to fight against unfair social practises like child marriage and the devdasi system. Dr. Ambedkar tried to make sure that women's rights were a part of India's political language and constitution. He insisted that the Hindu Code bill include the most important changes and improvements. He also insisted and asked every member of parliament to help get the bill passed in parliament. In the end, he quit for the same reason. So, every sentence and word he says shows how much he cares about women and wants them to grow in every way.